Improving Visualization Methods of Utility-Weighted Disability Outcomes for Stroke Trials - Tokunboh, Ivie; Sung, Eleanor Mina; Chatfield, Fiona; Gaines, Nathan; Nour, May; Starkman, Sidney; Saver, Jeffrey L. (Frontiers in Neurology, 2022)
Background: The modified Rankin Scale (mRS) is the most common endpoint in acute stroke trials, but its power is limited when analyzed dichotomously and its indication of effect size challenging to interpret when analyzed ordinally. To address these issues, the utility-weighted-mRS (UW-mRS) has been developed as a patient-centered, linear scale. However, appropriate visual displays of UW-mRS results are needed, as current stacked bar chart displays do not convey crucial utility-weighting information. Design/Methods: Two UW-mRS display formats were devised: 1) Utility Staircase charts, and 2) choropleth-stacked-bar-charts (CSBCs). In Utility Staircase displays, mRS segment height reflects the utility value of each mRS level. In CSBCs, mRS segment color intensity reflects the utility of each mRS level. Utility Staircase and CSBC figures were generated for 15 randomized comparisons of acute ischemic/hemorrhagic stroke therapies, including fibrinolysis, endovascular reperfusion, blood pressure moderation, and hemicraniectomy. Results: Utility values outcomes were: 1 for mRS 0; 0.91-mRS 1; 0.76-mRS 2; 0.65-mRS 3; 0.33-mRS 4; 0-mRS 5; 0-mRS 6. The Utility Staircase and CSBC displays rapidly conveyed patient-centered valuation of trial outcome distributions not available in convention ordinal stacked bar charts. Tufte-lie-factor (LF) scores indicated “substantial distortion” of utility-valued outcomes for 93% (14/15) of conventional stacked bar charts, versus “no distortion” for all Utility Staircase and CSBC displays. Clinician ratings on the Figural Display Questionnaire indicated that utility information encoded in row height (Utility Staircase display) was more readily assimilated than that conveyed in segment hue intensity (CSBC), both superior to conventional stacked bar charts. Conclusions—Utility Staircase displays are an efficient and preferred graphical format for conveying utility weighted – modified Rankin Scale primary endpoint results of acute stroke trials, and choropleth-stacked-bar-charts a good alternative. Both are more accurate in depicting quantitative, health-related quality of life results, and preferred by clinician users, compared with conventional stacked bar charts.